Turismo de aventura para diversificar la oferta en la reserva de producción de fauna Chimborazo - Baldeón Castillo, Leonardo Mauricio (2018)
The purse of the research project is the elaboration of adventure tourism products, as a way to diversify affer of the reserve. The main problem is a poor supply of adventure tourism products, it found worn out products, missing routes, attractions and activities. The research was conducted in the Chimborazo Fauna production Reserve, Whit a height 6310 msnm and an extension of 58.560 ha, shared by the Tungurahua, Chimborazo and Bolivar provinces. The general objective of the research is the creation of tourism products order to diversity the tourism offer, through the specific objective which are to establish a baseline to know the actual state of tourism in the reserve, continuing whit the elaboration of an inventory of tourist attractions, routes and adventure activities, ending with the production of tourist products of adventure. The tourism products seek to diversify the supply in The Chimborazo Fauna production Reserve, field research was conducted through visit to the sector, allowing to know natural resources and identify tourist services, bibliographic research through the collection and analysis of information related, the research was developed based on tourist s who visited the Wildlife Production Reserve in 2017, the sample size was extracted by applying the corresponding by applying the corresponding statistical formula. In conclusion is to create adventure tourism products taking advantage of all the attractions and routes that the reserve has it.